Statistik terapan untuk penelitian ilmu sosial : (teori dan praktik dengan IBM SPSS statistic 21 /Burhan Nurgiyantoro, Gunawan, Marzuki - BURHAN NURGIYANTORO; Burhan Nurgiyantoro; Gunawan; Marzuki (Gadjah Mada University Press, 2015)
xiii, 479 hlm. : ilus. ; 22 cm.